Fasciculations demonstrate daytime consistency in amyotrophic lateral sclerosis. Issue 6 (7th April 2020) - Bashford, James; Masood, Urooba; Wickham, Aidan; Iniesta, Raquel; Drakakis, Emmanuel; Boutelle, Martyn; Mills, Kerry; Shaw, Chris
Abstract: Introduction: Fasciculations represent early neuronal hyperexcitability in amyotrophic lateral sclerosis (ALS). To aid calibration as a disease biomarker, we set out to characterize the daytime variability of fasciculation firing. Methods: Fasciculation awareness scores were compiled from 19 ALS patients. In addition, 10 ALS patients prospectively underwent high‐density surface electromyographic (HDSEMG) recordings from biceps and gastrocnemius at three time‐points during a single day. Results: Daytime fasciculation awareness scores were low (mean: 0.28 muscle groups), demonstrating significant variability (coefficient of variation: 303%). Biceps HDSEMG recordings were highly consistent for fasciculation potential frequency (intraclass correlation coefficient [ICC] = 95%, n = 19) and the interquartile range of fasciculation potential amplitude (ICC = 95%, n = 19). These parameters exhibited robustness to observed fluctuations in data quality parameters. Gastrocnemius demonstrated more modest levels of consistency overall (44% to 62%, n = 20). Discussion: There was remarkable daytime consistency of fasciculation firing in the biceps of ALS patients, despite sparse and intermittent awareness among patients' accounts.